PENGEMBANGAN BAHAN AJAR BIOMAGAZINE BERBASIS BRAIN- BASED LEARNING (BBL) PADA MATERI SISTEM RESPIRASI DISERTAI VIDEO DAN TEKA-TEKI SILANG UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Nuroktavia, Riska; Prihatin, Jekti; Wahono, Bevo (Bio-Lectura : Jurnal Pendidikan Biologi, 2023)
The development of teaching materials into important media to support success in the learning process, one of the interesting and interactive teaching materials to be developed is biomagazine. This research is research and development (Research and Development) which aims to produce valid, practical, and effective biomagazine teaching materials to increase student motivation and learning outcomes. The research model used is the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the development are in the form of biomagazine teaching materials on the respiratory system material presented based on Brain-Based Learning (BBL) accompanied by videos and crossword puzzles. Validity is obtained through the average validation value of material experts, media experts, and development experts as well as user experts of 86.89 with a very valid category. Practicality was obtained through the average observed practicality score of 88.24 in the very practical category, the legibility test was 97.22 in the very easy category, and the practicality of student responses was 88.45 in the very practical category. Effectiveness is obtained based on improving students' cognitive learning outcomes for three consecutive meetings using the N-gain test of 0.70; 0.70; and 0.71 in the high category and the value of increasing students' ARCS learning motivation of 92.01 on the attention indicator, 92.43 on the relevance indicator, 92.22 on the confidence indicator, and 91.94 on the indicator of satisfaction (satisfaction) with a very good category. The developed biomagazine teaching materials can be used as alternative teaching materials for teachers and students improve motivation and student learning outcomes in Indonesia